CHRONIC ADMINISTRATION OF METHYLMERCURY ALTERS COGNITIVE AND MITOCHONDRIAL DYSFUNCTION IN RAT CEREBELLUM – A NOVEL APPROACH TO THERAPY FOR MINAMATA DISEASE BY A MEDHYA RASAYANA DRUG BACOPA MONNIERA - JOHNSON CHRISTINAL,; THANGARAJAN SUMATHI, (International Journal of Pharma and Bio Sciences, 2014)
Methylmercury (MeHg) is a highly toxic environmental pollutant that causes severe neurological disorders. Considering the neuroprotective property of Bacopa monniera, this study was aimed to evaluate protective effect of Bacopa monniera extract (BME) against MeHg induced mitochondrial dysfunction. Rats were exposed to MeHg by gavage (5mg/kg, b.w) and BME was administered (40 mg/kg, orally) 1 hour before of MeHg for 21 days. After treatment period, MeHg exposure significantly increased the immobility time and decreased learning memory. MeHg exposure resulted in DNA fragmentation and Cytochrome c release in cerebellum of rat. BME pre-treatment reverted all the above changes to near normal. Activities of neurotransmitter enzymes MonoamineOxidase (MAO), Acetyl cholinesterase (AChE), Choline acetyltransferase (ChAT) and Electron Transport Chain (ETC) enzymes were found to be decreased after MeHg exposure. Pre-treatment with BME significantly increased the enzyme activities in cerebellum. The results highlighted that Bacopa monniera can alleviate the MeHg induced mitochondrial dysfunction in rat cerebellum.